Metofluthrin: investigations into the use of a volatile spatial pyrethroid in a global spread of dengue, chikungunya and Zika viruses - Buhagiar, Tamara S. (Parasit Vectors, 2017)
BACKGROUND: Metofluthrin reduces biting activity in Aedes aegypti through the confusion, knockdown, and subsequent kill of a mosquito. A geographical spread in dengue, chikungunya, and Zika viruses, increases intervention demands. Response to a Zika outbreak may require a different strategy than dengue, as high-risk individuals, specifically pregnant women, need to be targeted. METHODS: In semi-field conditions within a residential property in Cairns, Queensland, the impacts of metofluthrin on biting behaviour of free-flying Wolbachia-infected Ae. aegypti were evaluated. RESULTS: Mortality in Ae. aegypti exposed to metofluthrin over a 22 h period was 100% compared to 2.7% in an untreated room. No biting activity was observed in mosquitoes up to 5 m from the emanator after 10 min of metofluthrin exposure. Use of metofluthrin reduced biting activity up to 8 m, regardless of the host’s proximity (near or far) to a dark harbourage area (HA) (P < 0.0001 and P = 0.006), respectively. In the presence or absence of the metofluthrin emanator, the host was most likely bitten when located immediately next to a HA (within 1 m) versus 8 m away from the HA (P = 0.006). The addition of a ceiling fan (0.8 m/s airflow) prevented all biting activity after 10 min of metofluthrin exposure. Previously unexposed Ae. aegypti were less likely to reach the host in a metofluthrin-treated room [Formula: see text] = 31%) compared to an untreated room ([Formula: see text] ) (P < 0.0001). In a treated room, if the mosquito had not reached the host within 30 s, they never would. Upon activation, the time required for metofluthrin to infiltrate protected locations within a room causing knockdown in caged mosquitoes, required more time than exposed locations (P < 0.003); however exposed and protected locations do eventually reach equilibrium, affecting mosquitoes equally throughout the room. CONCLUSION: Metofluthrin is effective in interrupting indoor host-seeking in Ae. aegypti. Metofluthrin’s efficacy is increased by centrally locating the emanator in the room, and by using a fan to increase airflow. Newly treated rooms may require a period of 2–4 h for sufficient distribution of the metofluthrin into protected locations where mosquitoes may be resting.